Transient Institutional Ownership and CEO Contracting - Dikolli, Shane S.; Kulp, Susan L.; Sedatole, Karen L. (The Accounting Review, 2009)
ABSTRACT: Prior research documents that CEOs respond to transient ownership preferences by choosing actions to meet short-term earnings targets. This study examines whether contract designers anticipate these actions and respond by adjusting explicit CEO compensation contracts. We find that, in determining CEO cash bonuses, firms with high levels of transient investors, on average, place a relatively low weight on earnings and a relatively high weight on annual returns. Additionally, both the likelihood of granting equity and the magnitude of annual equity grants to CEOs are higher with a higher level of transient investors, after controlling for previously studied determinants of equity grants. The results suggest transient-owner trading behavior creates implicit incentives for CEOs to take actions that increase current earnings, and firms take these implicit incentives into account in the design of explicit CEO compensation contracts.